Perlindungan Hukum Bagi Penumpang Angkutan Umum Tanpa Izin yang Mengalami Kerugian dalam Perspektif Hukum Perdata Positif - Deity Yuningsih (Al-'Adl, 2016)
It cannot be denied in fact in the community that there are still vehicle that does not legal night used as an instrument transportation public transport of a motorcycle ( ojek ) and private cars. It generated problems in legal matters relating to legal protection for loss for passengers that undergoes them, so important a research.Type research used is research law normative, with the approach regulations and conceptual.The research results show that passengers who had losses lives and or goods due to had an accident during in the transport of from the perspective of civil law positive is in a position very weak to shelter law have compensation, good based on an agreement transportation, based on act number 33 1964 about funds account must accident passengers, and act number 34 1964 about funds account must accidents on the road.